Tissue-Specific Modulation of Spexin Expression in Diet-Induced Obese Male Rats: Comparative Effects of Aerobic Exercise and Metformin - Aydemir, Isa; Cinar, Vedat; Akbulut, Taner; Yalcin, Mehmet Hanifi; Yasul, Yavuz; Gencer, Berrin Tarakci; Bragazzi, Nicola Luigi (Mdpi, 2025)
Obesity, a major global health concern, is associated with systemic metabolic dysregulation. Spexin, a peptide implicated in appetite control and energy balance, may represent a biomarker and therapeutic target in obesity management. This study aimed to investigate tissue-specific modulation of spexin expression in obese male rats subjected to aerobic exercise and/or metformin treatment. Thirty-six Sprague-Dawley rats were randomly assigned to six groups (n = 6 per group): (i) control, (ii) obese control, (iii) exercise, (iv) metformin, (v) metformin + exercise, and (vi) a decapitation baseline group. Obesity was induced via a 12-week high-calorie diet. Subsequently, interventions were applied over 4 weeks: treadmill running (30 min/day, 5 days/week) and/or metformin (150 mg/kg/day). Post-intervention, body weight significantly decreased in intervention groups (p < 0.001) exercise (-13.7%), metformin (-14.6%), and metformin + exercise (-21.1%) compared to the obese control group. ELISA revealed tissue-specific effects on spexin expression. In skeletal muscle, spexin levels were highest in controls (628 +/- 160.5 pg/mL), with a significant reduction in the metformin + exercise group (349 +/- 84.7 pg/mL; p = 0.003, Cohen's d = 2.17). In the liver, the control group showed the highest expression (443 +/- 240.8 pg/mL), while metformin + exercise yielded the lowest (254 +/- 20.4 pg/mL). In contrast, heart tissue maintained elevated spexin levels across all intervention groups, with the metformin + exercise group nearly matching control levels (617 +/- 25.2 vs. 618 +/- 53.2 pg/mL). Immunohistochemistry confirmed these patterns, with the highest cardiac histoscore in the metformin + exercise group (2.34 +/- 0.09). Hierarchical clustering underscored distinct tissue-specific expression patterns, separating muscle from liver and heart. Collectively, these findings suggest that spexin is differentially regulated by exercise and metformin, with joint effects and complex, tissue-specific modulation. This highlights spexin's potential as a biomarker and therapeutic target in precision obesity interventions.
Keywords: obesity; exercise; metformin; spexin; immunohistochemistry; hierarchical clustering